2017
DOI: 10.1080/00918369.2017.1374062
|View full text |Cite
|
Sign up to set email alerts
|

BDSM Role Fluidity: A Mixed-Methods Approach to Investigating Switches Within Dominant/Submissive Binaries

Abstract: This mixed-methods study of BDSM investigates the nuances of BDSM participants' role identities, role frequencies, and role fluidities-shifts in identities and play across time, location, scene, and play partner. Data were gathered from 202 online surveys and 25 semistructured interviews about participants' roles given their gender and sexual identities. These data reveal that men tend to self-identify as Dominant, Master, Top, or Sadist (DMTS) and always perform dominant roles, while women tend to self-identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Wismeijer & Van Assen 71 similarly found that 70% had a higher education (ie, bachelor’s or master’s degree), as compared with 34% in the general population. Martinez 35 again showed that about half of their BDSM sample had a college degree, with another 33% having taken up to 1 year of college. In this line, they also had higher income levels than the general population 2 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Wismeijer & Van Assen 71 similarly found that 70% had a higher education (ie, bachelor’s or master’s degree), as compared with 34% in the general population. Martinez 35 again showed that about half of their BDSM sample had a college degree, with another 33% having taken up to 1 year of college. In this line, they also had higher income levels than the general population 2 .…”
Section: Resultsmentioning
confidence: 97%
“…In the layman’s view, BDSM is subject to binary categorization, with participants being either dominant or submissive. More recently, however, more roles have been defined for BDSM community members to identify with: dominant, master/mistress, top, sadist, submissive, bottom, masochist and switch,34, 35 although a clear delineation between these roles does not always exist. In Martinez’s survey study, 35 most of the participants (n = 185 of 202) identified with 1 BDSM identity, with 41.1% of the participants self-identifying as a submissive, slave, or bottom, 28.2% as dominant, master, or sadist, and 22.3% as switch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A note about these findings is required at this stage. Previous studies of BDSM have noted in their samples that practitioners often come from a more educated background (Wismeijer & Assen, 2013) or higher socio-economic status (Martinez, 2018;Sandnabba et al 1999). However, one professional domme suggested that the educational status evidence was at odds with her not insubstantial practice, stating that she: "saw clients, none of whom are thick, [a British idiom for less intelligent,] but more tradespeople than professionals-perhaps they've got more disposable income?"…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The other important background point is that BDSM roles tend to be highly gendered: cis men are more likely to be Tops, cis women are more likely to be bottoms, and others are more likely to be switches (Martinez, 2018;Simula, 2012). My own figures in Table 2 are based on the roles that people with medium or high scene involvement claimed as their general preference, not necessarily the ones they actually performed.…”
Section: Setting the Scenementioning
confidence: 99%